2002
DOI: 10.1182/blood-2002-02-0388
|View full text |Cite
|
Sign up to set email alerts
|

Wiskott-Aldrich syndrome in a female

Abstract: Wiskott-Aldrich syndrome (WAS) is an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 42 publications
2
30
0
1
Order By: Relevance
“…Expression of the WASP transgene confers a selective growth advantage to transduced T cells as described in spontaneous reversions of WAS patients [29][30][31] as well as in other models of CD3-activated WASp + cells. 32,33 This observation indicates that the protein expressed in WW-transduced cells is functional. Furthermore, we have found that transduction of WAS-deficient T cells with the WW vector results in full reconstitution of cellular defects, including restoration of morphology and CD3-mediated responses (our unpublished data).…”
Section: Lentiviral Vectors Transcriptionally Targeted To Hematopoietmentioning
confidence: 87%
See 1 more Smart Citation
“…Expression of the WASP transgene confers a selective growth advantage to transduced T cells as described in spontaneous reversions of WAS patients [29][30][31] as well as in other models of CD3-activated WASp + cells. 32,33 This observation indicates that the protein expressed in WW-transduced cells is functional. Furthermore, we have found that transduction of WAS-deficient T cells with the WW vector results in full reconstitution of cellular defects, including restoration of morphology and CD3-mediated responses (our unpublished data).…”
Section: Lentiviral Vectors Transcriptionally Targeted To Hematopoietmentioning
confidence: 87%
“…[29][30][31][32][33] Therefore, HVS-WAS/1 cells were transduced with the WW lentiviral vector at MOIs of 0.01, 0.1 and 1 and kept in culture for 39 days. The percentage of WASpexpressing cells was analyzed by flow cytometry at days 7, 27 and 39 after transduction.…”
Section: Wasp Expression Confers a Selective Growth Advantage To Ww-tmentioning
confidence: 99%
“…Her daughter, completely free of XLT symptoms, was also heterozygous for the WASP mutation, but presented a random pattern of X-chromosome inactivation. Females with clinical signs of WAS and a random pattern of X-inactivation have also been described, although in all cases the causative mutation presented a strong WAS phenotype in the male offspring of the family, thus suggesting a major impact of the mutations in WASP protein alteration (23)(24)(25). The data appear to indicate that in XLT mutations an aberrant strong skewed X-inactivation pattern is required to develop clinical symptoms in female carriers.…”
Section: Discussionmentioning
confidence: 88%
“…Several of the clinical characteristics and laboratory findings in the patient resemble those found in WAS. They include recurrent infections, eczematous skin rash, thrombocytopenia, T cell lymphopenia affecting (Lutskiy et al, 2002;Proust et al, 2005). Western blot analysis revealed no detectable WASP in lysates of the patient's PHA T blasts (Fig.…”
Section: Expression Of Wip In the Patient's Cells Corrects The Defectmentioning
confidence: 99%